ANALISIS PENILAIAN TINGKAT RISIKO ERGONOMI TERHADAP KENYAMANAN PEKERJA PADA PT. WAHANA BARAMETAL PEKANBARU - William Wijaya; Samsir Samsir; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Awkward posture is one of the ergonomic risk contained in the workers, awkward postures that aren’t normaly done performed by these workers can cause stress on physical conditions of workers who have an impact on the incidence of injury to workers. To prevent injury from happening, it is necessary to conduct evaluation of ergonomic risk level on workers. This research is done through direct observation of all stages of the workers who do welding works. The assesment of ergonomic risk level uses Rapid Entire Body Assessment (REBA) methods, and Ovako Working Analysis System (OWAS). The population of this research include all of the ten workers who did metal welding process who works on PT. Wahana Barametal Pekanbaru. The results of research showed that: 1) metal cutting activities has an average ergonomic risk, 2) carrying iron activities has a high ergonomic risk, 3) welding activities has an average ergonomic risk, 4) grinding activities has a slightly high ergonomic risk, 5) painting activities has a high ergonomic risk. To reduce ergonomic risk level is necessary to change the action and the movement of workers, the provision of working tools and changes in the design of workers.Keywords : Ergonomic Risk Assessment, REBA, OWAS, Ergonomy.